EVALUASI PENERAPAN PENANGANAN PERTAMA CEDERA OLAHRAGA DENGAN METODE RICE PADA KLUB SEPATU RODA KARAWANG - Zuffar Alghifary, Fathan; Setiawan, M. Arief; Wijaya, Habibi Hadi (JURNAL ILMU KEOLAHRAGAAN, 2025)
This research aims to evaluate the application of the RICE method in the first aid treatment of sports injuries at the Karawang Roller Skate Club. The research method used is qualitative with a discrepancy evaluation approach, which compares standard injury treatment procedures with actual implementation in the field. Data was obtained through observation, interviews, and documentation from 12 informants consisting of coaches, athletes, and officials. The results showed that several aspects, such as the use of bandages (100%), ice compression for 15–20 minutes (100%), and follow-up injury evaluation (100%) had been implemented well. However, several significant gaps were found, such as compression duration for 48 hours (42%), elevation of the injured area (67%), and the availability of ice boxes (50%). These findings indicate the need for improved technical education, provision of supporting facilities, and the development of more systematic SOPs to optimize injury management.